Correlation Between Knee Muscle Strength and Maximal Cycling Speed Measured Using 3D Depth Camera in Virtual Reality Environment - Ye Jin Kim; Hye-seon Jeon; Joo-hee Park; Gyeong-Ah Moon; Yixin Wang (Korean Research Society of Physical Therapy, 2022)
Background: Virtual reality (VR) programs based on motion capture camera are the most convenient and cost-effective approaches for remote rehabilitation. Assessment of physical function is critical for providing optimal VR rehabilitation training; however, direct muscle strength measurement using camera-based kinematic data is impracticable. Therefore, it is necessary to develop a method to indirectly estimate the muscle strength of users from the value obtained using a motion capture camera.Objects: The purpose of this study was to determine whether the pedaling speed converted using the VR engine from the captured foot position data in the VR environment can be used as an indirect way to evaluate knee muscle strength, and to investigate the validity and reli-ability of a camera-based VR program.Methods: Thirty healthy adults were included in this study. Each subject performed a 15-sec-ond maximum pedaling test in the VR and built-in speedometer modes. In the VR speedom-eter mode, a motion capture camera was used to detect the position of the ankle joints and automatically calculate the pedaling speed. An isokinetic dynamometer was used to assess the isometric and isokinetic peak torques of knee flexion and extension.Results: The pedaling speeds in VR and built-in speedometer modes revealed a significant-ly high positive correlation (r = 0.922). In addition, the intra-rater reliability of the pedal-ing speed in the VR speedometer mode was good (ICC [intraclass correlation coefficient] = 0.685). The results of the Pearson correlation analysis revealed a significant moderate positive correlation between the pedaling speed of the VR speedometer and the peak torque of knee isokinetic flexion (r = 0.639) and extension (r = 0.598).Conclusion: This study suggests the potential benefits of measuring the maximum pedal-ing speed using 3D depth camera in a VR environment as an indirect assessment of muscle strength. However, technological improvements must be followed to obtain more accurate estimation of muscle strength from the VR cycling test.